Apply the distributive property to create an equivalent expression. ( 1 -2g +4h)\cdot 5 =(1−2g+4h)⋅5=left parenthesis, 1, minus, 2, g, plus, 4, h, right parenthesis, dot, 5, equals

Respuesta :

Answer:

5 - 10g + 20h

Step-by-step explanation:

Given three elements A, B and C related together according to the expression A(B+C), according to distributive property, the element A will be distributed to the rest of the element as shown;

A(B+C) = A(B)+A(C)

A(B+C) = AB + AC (Law of distributivity)

Given the expression according to the question (1−2g+4h)⋅5, in order to use the distributive law to find the equivalent expression, we will use the concept above as shown;

= (1−2g+4h)⋅5

= 5.(1−2g+4h)

= 5(1)-5(2g)+5(4h)

= 5 - 10g + 20h

Hence the equivalent expression using the distributive property is 5 - 10g + 20h

Answer:

5 - 10g + 20h